2021
DOI: 10.3389/fnins.2021.771980
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Fiber Materials as Implantable Depth Neural Electrodes

Abstract: Implantable brain electrophysiology electrodes are valuable tools in both fundamental and applied neuroscience due to their ability to record neural activity with high spatiotemporal resolution from shallow and deep brain regions. Their use has been hindered, however, by the challenges in achieving chronically stable operations. Furthermore, implantable depth neural electrodes can only carry out limited data sampling within predefined anatomical regions, making it challenging to perform large-area brain mappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…But because the bending stiffness scales with electrode size to the fourth power [41,42], any further increase in the insulation thickness will increase the stiffness of the electrodes, which is associated with a higher level of inflammatory responses, glial encapsulation, and neuronal degeneration, thus impairing the long-term stability of the recordings. It was reported that by sandwiching nanometer-thick inorganic oxide layers from atomic layer deposition inside the polymer insulation, the stability of the CNTF electrode's electrochemical properties were significantly improved as shown by the in vitro accelerated aging tests [63]. The extra inorganic layers do not significantly compromise the mechanical compliance of the CNTF electrodes due to their nanometer thickness.…”
Section: Discussionmentioning
confidence: 99%
“…But because the bending stiffness scales with electrode size to the fourth power [41,42], any further increase in the insulation thickness will increase the stiffness of the electrodes, which is associated with a higher level of inflammatory responses, glial encapsulation, and neuronal degeneration, thus impairing the long-term stability of the recordings. It was reported that by sandwiching nanometer-thick inorganic oxide layers from atomic layer deposition inside the polymer insulation, the stability of the CNTF electrode's electrochemical properties were significantly improved as shown by the in vitro accelerated aging tests [63]. The extra inorganic layers do not significantly compromise the mechanical compliance of the CNTF electrodes due to their nanometer thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Soft and stretchable substrates are better matched to the stiffness of the brain tissue. Common flexible neural electrode materials include carbon-based fibers, , conductive polymers (poly­(3,4-ethylene­dioxythiophene)-poly­(styrene­sulfonate) (PEDOT:PSS)), polydopamine, etc. The use of flexible polymer substrates to design microarrays is also a promising strategy for structuring electrode flexibility.…”
Section: Strategies To Reduce Immune Response Of Implantable Neural M...mentioning
confidence: 99%
“…In recent years, various carbon-based conductive materials have been used to prepare flexible implantable electrodes to reduce the inflammatory response, such as carbon nanotube (CNT) fibers, carbon fibers, and graphene fibers. , Two-dimensional graphene with a single atomic layer is used as a conductive material for the preparation of neural electrodes with many advantages such as high mechanical compatibility for close contact with the brain tissue interface and good electrical conductivity and carrier mobility up to 100,000 cm 2 V –1 s –1 much higher than silicon. The characteristic roughness and high porosity of graphene can reduce the impedance of electrodes prepared from it and improve the charge injection capacity, thus enabling high-quality neural recordings.…”
Section: Strategies To Reduce Immune Response Of Implantable Neural M...mentioning
confidence: 99%
“…Currently, researchers are employing coating strategies to modify the surfaces of electrodes. One approach involves the use of nanomaterials, such as Pt black and CNT coatings, which increase the surface active sites of the electrodes, lowering the interfacial impedance and thus enhancing the sensitivity of neural signal recording. However, nanomaterials as electrode surface modifications may degrade over time and leave residues, posing risks in terms of biocompatibility and safety. The second type involves the modification with a conductive polymer, such as PEDOT, PPy, and PDMS, which reduce impedance and enhance charge injection capacity. Additionally, these modifications allow for better adaptation to the surface of biological tissues during implantation, reducing damage to the tissues. However, deformation of the electrodes during implantation can lead to performance degradation, and poor environmental conditions and long-term use may lead to layering and failure of the coating due to the high environmental stability requirements of conductive polymer materials .…”
Section: Introductionmentioning
confidence: 99%